PENGARUH METFORMIN DOSIS RENDAH JANGKA PENDEK TERHADAP RISIKO BERKEMBANGNYA MENJADI DM TIPE-2 PADA PREDIABETES NON OBES - Hardiman, Djoko (Medicina, 2012)
Metformin was reported to decrease the risk of type-2 DM establishment in the obese prediabetic individual. While whether low-dose short-term metformin administration decrease the risk of type-2 DM establishment in the non-obese prediabetic individual was not yet reported so far. The study was to determine if insulin resistance control by low-dose short-term metformin administration in the non-obese prediabetic individual might decrease the risk of type-2 DM establishment. The present study was prospective, experimental study with pretest-posttest control group design. It was conducted on the first degree relative of the type-2 DM patient who met the criteria of non obese prediabetic individual. Subjects were randomly classified into treatment group (designed for metformin administration), and the control group (designed for placebo administration). The prediction of atherosclerosis risk was based on the formula of Insulin Resistance In dex (IRI). The results show that significant difference between pre and post metformin administration term were p=0.003, p=0.051 and p=0,259 for insulin level, insulin 2 hrs postprandial and IRI in the treatment and control group, respectively. While for the fasting glucose level and glucose 2 hrs post-prandial level, the significant differences were p=0.004 and p=0.395 in the treatment and control group, respectively. The study concluded that the low-dose short-term metformin administration might significantly decrease the risk of type-2 DM establishment in the non-obese prediabetic individual.
Keywords: metformin, non-obese prediabetic, type-2 DM